Pengenalan Gerak Non Lokomotor Pada Siswa-Siswi Sekolah Dasar - ALFAREZA, DAFFA ZIDANE; Ardhana, Naufal Pramuditya; Putri, Nur Annisa; Putri, Mega Widya (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2024)
Article of service to elementary school students through the introduction of non-locomotor movement in partnership with elementary school students located at SDN 03 Kedungwuni, Gembong Gang Beringin 1 No. 23 Kedungwuni sub-district, Kedungwuni, there were 7 female students and 11 students who took part in this activity. The program carried out with partners is the introduction of non-locomotor movement. The method of implementing this activity is carried out by mutual agreement, this service activity is given in 1 meeting within 2 hours, this service will be carried out on Friday 17 November 2023 at 07:00 WIB to 09:00 WIB in the elementary school yard of SDN 03 Kedungwuni. The results achieved from this activity were that the female students had better non-locomotor movements